INTRUSION DETECTION SYSTEM FOR CLOUD SYSTEM USING INTELLIGENT AGENTS (International Journal of Engineering and Computer Science, 2013)
Cloud computing allows the end users to use the application without installation and access their personal files at any computer with internet access. Apart from the advantages of cloud environment, security is the major issue. Due to the distributed nature, cloud environment is an easy target for intruders looking for the possible attacks to exploit. To address the security issues in the cloud environment an Intrusion Detection System (IDS) is proposed based on the features of the mobile agent. The mobile agents are used to collect and analyze the data collected from cloud environment to identify attacks exploited by the intruders. The main objective of the proposed system is to detect the known and unknown attacks exploited by the intruders in the cloud environment.